2018
DOI: 10.1111/ssm.12271
|View full text |Cite
|
Sign up to set email alerts
|

Digital game‐based learning for K–12 mathematics education: A meta‐analysis

Abstract: Digital games (e.g., video games or computer games) have been reported as an effective educational method that can improve students' motivation and performance in mathematics education. This meta‐analysis study (a) investigates the current trend of digital game‐based learning (DGBL) by reviewing the research studies on the use of DGBL for mathematics learning, (b) examines the overall effect size of DGBL on K‐12 students' achievement in mathematics learning, and (c) discusses future directions for DGBL researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 36 publications
3
63
1
2
Order By: Relevance
“…The investigated games differed in the degree to which they provided cognitive scaffolding and offered opportunities for proficiency development and reflection upon learning strategies. In a recent meta-analysis which included 17 studies, Byun and Joung (2018) found an overall weighted effect size of d = 0.37 for the relative effectiveness of digital games for learning mathematics. Yet, effect sizes vary largely between the analyzed studies.…”
Section: Digital Game-based Learning Research: Current Practice and Fmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigated games differed in the degree to which they provided cognitive scaffolding and offered opportunities for proficiency development and reflection upon learning strategies. In a recent meta-analysis which included 17 studies, Byun and Joung (2018) found an overall weighted effect size of d = 0.37 for the relative effectiveness of digital games for learning mathematics. Yet, effect sizes vary largely between the analyzed studies.…”
Section: Digital Game-based Learning Research: Current Practice and Fmentioning
confidence: 99%
“…Often multiple measurement points are reported, differing in time intervals between measurements (Bottino et al, 2007;Kebritchi et al, 2010;Habgood and Ainsworth, 2011;Bai et al, 2012;Shin et al, 2012;Bakker et al, 2015). Methodologies entail qualitative, quantitative, and mixed methods, with the latter two being the most prevalent (for a comprehensive overview, see Byun and Joung, 2018).…”
Section: Digital Game-based Learning Research: Current Practice and Fmentioning
confidence: 99%
See 1 more Smart Citation
“…When learning through games, students typically take greater interest in and have more opportunities for discovering, talking, exploring, and questioning (Perini et al, ; Yang, ). However, the use of GBL does not guarantee that learners will consistently achieve better learning results because it is not possible to identify a clear causal relationship between students' gameplay experiences and academic performance (Byun & Joung, ; Meluso et al, ; Wrzesien & Raya, ). As O'Neil, Wainess, and Baker () articulated, educational GBL should take the prior knowledge and life experiences of individuals into account in order to enhance learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar vein, Tokac et al (2019) highlight that video games are only a slightly effective teaching strategy for teaching mathematics at PreK-secondary levels. Moreover, Byun and Joung (2018) underline the need for more empirical research studies so as to more accurately determine the effect of electronic games on maths learning. According to Tokac et al (2019), there is a need for a more attentive approach to game design with respect to specific learning outcomes across various mathematical domains.…”
Section: Introductionmentioning
confidence: 99%